ENHANCEMENT EDUCATIONAL PROCESS IN THE CONDITIONS OF INFORMATIVE-COMMUNICATIVE PEDAGOGICAL ENVIRONMENT - Petukhova Л.Є. (Journal of Information Technologies in Education (ITE), 2010)
In the article are considered the possibilities and conditions of realization informative-communicative pedagogical environment at high school, the ways of educational process expansion in the context of informative-communicative pedagogical environment are also described.